Interactions between some plant-parasitic nematodes and Rhizoctonia solani in potato fields - Björsell, Pia (SLU/Dept. of Ecology, 2015)
The pathogenic fungus Rhizoctonia solani causes major economic losses for potato producers in Sweden. The producers, as well as advisors, have reported possible increases in severity of R. solani when free-living plant parasitic nematodes are present and active. There are several examples in the literature of interactions between pathogens where one, or both species, support or increase the damage made by the other organism. These complexes are important to investigate and to be able to forecast, since even low incidences of fungi or nematodes may result in an interaction of significance. The aim of this study was to investigate possible interactions between two different nematodes and the fungus R. solani under field conditions. The nematodes were root-lesion (Pratylenchus spp.) and stubby-root nematodes (Trichodoridae). The hypothesis was that there is spatial correlation in the distribution of free-living nematodes and the severity of stem canker caused by R. solani. A greater severity of stem canker is related to higher numbers of nematodes. Nematodes in the genus Globodera were also included after finding high numbers of these cyst nematode juveniles in the samples. The study was limited to sampling of eight potato fields with observed outbreaks of damping off in the northern part of the county of Östergötland, located in the middle part of Sweden. Both soil sampling and grading of stem canker were performed at a gradient starting from the center of the patch. The nematodes were first extracted and then identified and counted in the suspension from each extraction under high magnification. There was no difference in the number of nematodes within the fields (middle of the patch, at the border, close to healthy plants and the control) for any of the investigated nematodes. The severity of R. solani was greater on plants graded in the middle of the patches compared to those in the margins. The interaction between Trichodoridae and R. solani, as well as the interaction between Globodera spp. and R. solani, were both significant. There was no observed connection between Pratylenchus spp. and R. solani in this field study. These results partly confirm what potato producers and advisors have observed and will hopefully give them useful information for future decisions of appropriate management methods. Future work to untangle the mechanisms behind the interactions is needed.